2013
DOI: 10.15208/beh.2013.7
|View full text |Cite
|
Sign up to set email alerts
|

Affect of perceived barriers to entrepreneurship on the career choice decision of students: A study of Uttarakhand state, India

Abstract: In this study we have tried to evaluate the affect of perceived barriers to entrepreneurship on the career choice intentions of students with special reference to taking up entrepreneurship as a career choice. It is a quantitative study wherein we have taken data of 530 young students studying in the final year of various professional courses of Uttarakhand state of India. The results confirmed relationship between the strength of perceived barriers to entrepreneurship and their decision to take up entrepreneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
(6 reference statements)
2
9
0
Order By: Relevance
“…Likewise, the respondents from various age groups were similarly inspired by internal motives when planning their own business to a larger extent than by the external ones. Similar to other studies (Jafarnejad, Abbaszadeh, Ebrahimi, & Abtahi, 2013;Sharma & Madan, 2013;Smith & Beasley, 2011;Staniewski, 2009;Tanveer et al, 2011), our findings revealed that people who plan to start their own businesses perceive numerous burdensome obstacles. In the opinion of our respondents, the most harmful barriers were lack of experience, lack of capital and risk of failure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Likewise, the respondents from various age groups were similarly inspired by internal motives when planning their own business to a larger extent than by the external ones. Similar to other studies (Jafarnejad, Abbaszadeh, Ebrahimi, & Abtahi, 2013;Sharma & Madan, 2013;Smith & Beasley, 2011;Staniewski, 2009;Tanveer et al, 2011), our findings revealed that people who plan to start their own businesses perceive numerous burdensome obstacles. In the opinion of our respondents, the most harmful barriers were lack of experience, lack of capital and risk of failure.…”
Section: Discussionsupporting
confidence: 91%
“…Merely 8.3% of the students perceive the number of barriers to starting one's own business to be relatively small. The same study indicates quite an interesting correlation between the personality traits of the potential entrepreneur and the severity of the barriers to setting up a business (Sharma & Madan, 2013).…”
Section: Literature Reviewmentioning
confidence: 72%
“…This could possibly be attributed to the presence of Entrepreneurship subject taught in the MBA/PGDM and BHMCT courses and an additional credit is due to the dot com revolution which has possibly given some boost to the entrepreneurial inclination of students with technical back ground as it requires less capital investment in comparison to other ventures. Capital investment has already been found to be a major perceived barrier among the students of Uttarakhand (Sharma & Madan, 2013). This research has given us a direction to further explore the impact of family, society & culture of Uttarakhand in building entrepreneurial inclination and also determine the effectiveness of university education system of Uttarakhand in building entrepreneurial inclination.…”
Section: Resultsmentioning
confidence: 93%
“…In fact, nothing significant is seen in terms of entrepreneurship development from within the state. Some of the major perceived barriers to youth entrepreneurship identified in Uttarakhand are lack of capital, no prior experience and lack of guidance (Sharma & Madan, 2013). The growing educated, idle, jobless and underemployed youth is a major societal problem which if not tackled and controlled timely could turn into a bigger trouble for the state government.…”
Section: Introductionmentioning
confidence: 99%
“…Mat et al (2015) analyzed several factors and they found that locus of control, followed by need of achievement and subjective norms are more influential for the entrepreneurial intention. Sharma and Madan (2013) found that 41.89% students perceive the barriers to start a business seriously whereas 49.81% students perceive the barriers for the same reason moderately and only 8.3% students perceive that the barriers are comparatively lower. The study also revealed that most of the students believe that they will face a variety of hindrances to initiate a new venture.…”
Section: Literature Reviewmentioning
confidence: 93%